37 Del. Laws 813 (1931) - (:unkn) unknown (My University, 1931)
Ch. 249, § 1: Prohibited a person from possessing a machine gun. Punishable by fine and/or imprisonment.
Keywords: MACHINE GUN RESTRICTION